Plant Copper Metalloenzymes As Prospects for New Metabolism Involving Aromatic Compounds - Mydy, Lisa S.; Chigumba, Desnor N.; Kersten, Roland D. (Frontiers in Plant Science, 2021)
The provisional abstract of this article is not available; this page will be updated when the full version-of-record is published.